PTU-226 Prospective observational cohort study of laparoscopic versus open emergency stoma formation. (22nd June 2015) - Thomas, C; Allan, S; Harji, D; Coyne, P; Griffiths, B; Plusa, S
Abstract : Introduction: Emergency general surgery is a huge clinical service, with over a third of admissions secondary to colorectal pathology, including diverticular disease, colorectal malignancy and inflammatory bowel disease. This cohort of patients often requires surgical intervention with the formation of a stoma. There has been a steady rise in the use of laparoscopic surgery (LS) in the emergency colorectal surgery. The aim of this study is to investigate the role of LS in the colorectal emergency requiring a stoma. Method: A prospective observational cohort study was conducted between March 2013 and June 2014. All adult patients (>18 years old) undergoing an emergency operation as defined by NCEPOD guidelines resulting in the formation of a stoma were included. Data was analysed using SPSS version 22. Results: A total of 77 patients were identified, with 23 (29.9%) in LS group and 54 (70.1%) in the open surgery (OS) group. Conversion rate was 13%. Forty-two (54.5%) ileostomies and 35 (45.5%) colostomies were constructed. LS was associated with reduced morbidity and median length of stay. Conclusion: Emergency LS is a feasible and effective option in the colorectal emergency requiring a stoma, with improved clinical outcomes over OS. Disclosure of interest: None Declared.